Leaving Victorian Studies Behind: The Case of Vassar College. Issue 1 (1st June 2022) - Murdoch, Lydia; Zlotnick, Susan
Abstract : Much of the recent reflection on nineteenth-century global studies has focused on research, graduate program(me)s, or upper-level courses. This essay recounts the transformation of the Program in Victorian Studies at Vassar College, one of the few institutions in North America offering an undergraduate degree in Victorian Studies, into a global nineteenth-century studies program. The new multidisciplinary program prioritizes teaching at the 100-level in order to prepare students to take a global perspective into advanced courses. Its introductory team-taught course, 'Revolution, Evolution, and the Global Nineteenth Century', is the place where the Vassar faculty work out both the practical and theoretical challenges of teaching 'the global', such as how to incorporate non-Anglophone materials as well as science and technology into a global curriculum. The course – and the program more broadly – constitute a serious effort to decolonize the study of the nineteenth century at the undergraduate level.